Мужской день - Минаев Борис Дорианович (Самое время!, 2009)
7-9кл Экземпляры: аб (ретроконверсия) / Инвентарный номер: 44998 / Цена: 226.49 / Сис.шифр: Р2 / Авт.знак: М 61 / ГРНТИ: 17.82 / ББК: 84(2=411.2)6